Motif dan Makna Penggunaan Fitur SPaylater di Kalangan Mahasiswi Universitas Singaperbangsa Karawang - Siti Fauziyah Sabilah; Ana Fitriana Poerana; Nurkinan Nurkinan (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The increase in online shopping transactions due to the COVID-19 pandemic has prompted fintech companies to introduce Paylater services as a new payment method. One of the Paylater provider platforms is Shopee which is widely used in Indonesian society since the last two years especially among young people, including students at Singaperbangsa Karawang University. This study aims to determine the motives and meanings of using SPaylater for students at Singaperbangsa Karawang University. This research methode use qualitative methode with a phenomenological approach, because the researcher tries to find out the phenomenon from the experience of the informants directly, as well as the motives and meanings of the informants using SPaylater. The results of the study show first, the motive for using the SPaylater feature are just an experiments, suggested by friends, urgent need, and lazy to top-up Shopeepay. Second, the motive for (in-order-to motive) namely for managing finance, wanting to meet the need of clothes, wanting to buy what they like, and wanting to fulfil their shopping desires. Third, the meaning of SPaylater for female student is as a fulfillment of needs, a new way of credit for goods, budget suppression, and fulfilment of desires. Keywords: SPaylater; Students; Motives and Meanings.